Front Cover: Regiospecific Remote Pt–H Interactions in Oligomethylene‐Vaulted (N^C^N)‐Pincer PtII Complexes (Eur. J. Inorg. Chem. 44/2018). Issue 44 (22nd November 2018) - Komiya, Naruyoshi; Hosokawa, Takashi; Adachi, Junya; Inoue, Ryo; Kawamorita, Soichiro; Naota, Takeshi
Abstract : The Front Cover shows a view of the regiospecific activation of inactivated C–H bonds of long linear alkyl chains in oligomethylene‐vaulted pincer platinum(II) complexes. These unprecedented remote intramolecular Pt–H contacts were observed on the linker hydrogen atoms at specific positions in a highly regiospecific manner in both the solution and the solid state. More information can be found in theFull Paper by N. Komiya, T. Naota et al. For more on the story behind the cover research, see theCover Profile .